Pelatihan Bahasa Inggris Komunikatif Dalam Rangka Pengembangan Pura Dalem Ped Sebagai Objek Wisata Religi - I Ketut Subagia; Nyoman Sujaya; Anak Agung Inten Mayuni; Ni Nyoman Kertiasih (Postgraduated Community Service Journal, 2025)
This community service empowers the community in the field of communicative English knowledge. The target is pecalangs (the security) who work for the Dalem Ped temple. The service which gives training about communicative English aims at optimizing the pecalang's ability to communicate using English. This is necessary to be done so that the pecalang at the Dalem Ped temple are able to serve and supervise visitors who come not only from Bali and outside Bali but also from abroad so that service to visitors and order in maintaining the sanctity of the temple can be handled. The methods applied include direct observation, recording problems faced by partners, preparing modules and books, giving lectures, mentoring, simulations and evaluations. To increase understanding, the service team has also donated the book "English for Guides" written by the service team. Good communication, friendliness and enthusiasm of the partners in participating in the training made the training run well. The material could be delivered well and they already understand the basics of learning communicative English. They already understand simple English sentence patterns which are very effective for mastering English quickly. However, studying English requires high intensity because mastering English does not only require knowledge but also skills. Therefore, training like this needs to be carried out repeatedly. However, the service team remains optimistic and hopes that this training will be beneficial for both partners and the service team and the Warmadewa University institution.